SP7.2.4 Evaluation of Non-crosslinked Acellular Porcine Dermal Mesh – A Single Centre Experience. (28th October 2021) - Karri, Rama; Aamery, Amaar; Singh-Ranger, Deepak
Abstract: Aims: We report our experience with a cellular porcine dermal non-crosslinked biological mesh (EGIS®). We conducted a review of indications and outcomes of patients requiring the mesh for incisional hernia/complex abdominal wall reconstruction with component separation, parastomal hernia repairs and ELAPE. Patients were followed for a minimum of 6 and assessed for recurrence, seroma formation and chronic pain. Secondary outcome was the assessment of ease of use by the Surgeon – suturing and pliability. Method: A retrospective case notes review of patients requiring biological mesh (EGIS®) from 2016 to present. A qualitative survey about ease of use of EGIS® for operations studied was sent to all Consultant Surgeons. Results: EGIS® mesh was used in 38 patients: 23 Hernia repairs – 13 Incisional, 8 Parastomal, 2 Paraumbilical; 12 Pelvic floor repairs after ELAPE; and 3 abdominal wall reconstructions. Hernia recurrence occurred in 12 (32%), seroma 7 (18%) and chronic pain 7 (18%). The highest complications occurred in the incisional and parastomal hernia groups. Incisional hernia: recurrence in 5 (38%), seroma in 5 (38%) and chronic pain in 3 (23%). Parastomal hernia: recurrence in 3 (38%), chronic pain 2 (25%), seroma 1 (13%). Consultants scored the mesh 4.3 to 4.5 out of 10 for pliability, ease of use and suturing. Conclusion: Biological mesh is used to reinforce hernia repairs in contaminated or potentially contaminated fields. Non-crosslinked meshes are preferred for their greater cellular infiltration from host tissue with improved integration. Our experience with this mesh shows a high complication rate and requires re-evaluation.